2022
DOI: 10.1080/09537104.2022.2087868
|View full text |Cite
|
Sign up to set email alerts
|

Platelet inhibition by low-dose aspirin is not influenced by body mass or weight

Abstract: Supplemental Table 1. Correlations of aggregation of platelet-rich plasma with BMI and body weight in the primary cohort Correlation with BMI (r=) Correlation with weight (r=) AA (1.5mM) aggregation pre-ASA 0.02 -0.04 aggregation post-ASA -0.08 -0.15 Change in aggregation with ASA 0.07 0.13 % inhibition with ASA 0.06 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…15,16 Accordingly, we recently showed that in individuals without diabetes, neither body weight nor mass influenced platelet inhibition by either 81 mg or 325 mg of aspirin. 17 These observations together suggest that aspirin formulation may be responsible for the observed reductions in platelet inhibition, but that this mechanism is not wholly responsible for the observed differences in rates of MACE. Thus, to thoroughly dissect the robust findings of the meta-analysis, other mechanisms beyond aspirin-mediated COX-1 inhibition must be investigated.…”
Section: Introductionmentioning
confidence: 94%
“…15,16 Accordingly, we recently showed that in individuals without diabetes, neither body weight nor mass influenced platelet inhibition by either 81 mg or 325 mg of aspirin. 17 These observations together suggest that aspirin formulation may be responsible for the observed reductions in platelet inhibition, but that this mechanism is not wholly responsible for the observed differences in rates of MACE. Thus, to thoroughly dissect the robust findings of the meta-analysis, other mechanisms beyond aspirin-mediated COX-1 inhibition must be investigated.…”
Section: Introductionmentioning
confidence: 94%
“…Results of aspirin trials are further confounded by evidence that the dose required for optimal CV prevention may be influenced by weight, body mass, and the drug formulation. 20,21 A meta-analysis of 10 aspirin primary prevention trials 20 found the effect of low-dose aspirin (75-100 mg) to reduce CV events attenuated with increasing weight. In contrast, higher doses (≥325 mg) of aspirin showed a reverse interaction with weight, reducing CV events only at larger body size and increased weights.…”
Section: • the Recent United States Preventive Services Taskmentioning
confidence: 99%